Comparação das águas dos rios Jaguari e Atibaia na região de lançamento de efluente de indústria petroquímica - Oliveira, Eduardo Schneider Bueno de [UNESP] (2016)
The anthropic action in nature is a constant factor along the history, but each day the negative effects that it brings can be increasingly seen. Check these effects, its implications and what can be done in order to avoid bigger problems has a great importance to the manteinance of our planet in good conditions and, consequently, to the human being life quality. This study performs an analysis of the water quality of the Jaguari and Atibaia rivers, among which happens the dumping of residuals from a petrochemical industry, as well as of the quality of the water after its utilization process by the industry, before its devolution to the river. Thus, it is possible to verify this industry’s residual treatment quality and to analyze possible effects to the water quality after the residual dumping at the river. For this, based on data about fisical, chemical and microbiological characteristics of the water, appropriate statistical techniques are used, aiming to do the necessary analysis to fullfill the exposed intention. Because of the existence of dependency, methods that allow this ocurrence shall be used, such as the non parametric Blocks Bootstrap (K¨unsch, 1989; Politis & Romano, 1994). There is also the realization of multiple imputation, using the technique of the Distribution-free Multiple Imputation (Bergamo, 2007; Bergamo et al., 2008), once for some months there are missing data.